Study on kinetics of electro-optical and photoluminescent processes in nanostructured transition metal (W, Mo) oxide-based thin films - Le, Ha Chi (Đại học Quốc gia Hà Nội, 2017)
Electrochromic tungsten oxide films can be prepared by a variety of different techniques such as physical vapor [2] and chemical vapor deposition [14,29],electrochemical deposition [13,34], sol -gel [25], etc. The electrochemical deposition is expected to be one of the most economical methods for making a large-area film as well as automatically controlling the film growth. However, these transmittances as well as the durability of the films were still limited for practical use. The aim of this work is to improve electrochromic properties of WO3thin films deposited by electrochemical method. The morphology, electrochemical and optical properties concerning with electrochromic performance of the films are also discussed.